Acceptability of transcranial direct current stimulation in children and adolescents with ADHD: The point of view of parents. (January 2022) - Buchanan, Derrick Matthew; D'Angiulli, Amedeo; Samson, André; Maisonneuve, Alexander R; Robaey, Philippe
Transcranial direct current stimulation (tDCS) is a novel treatment option for attention deficit hyperactivity disorder. To facilitate translation into clinical practice, we interviewed parents of children who have experienced experimental tDCS. A grounded theory approach using open, axial, and selective coding provided seven emergent themes for acceptability: tDCS provides hope for parents, safety tolerability and side effects of tDCS versus medication, burden of treatment, education and trust with care providers, cost and coverage, unestablished tDCS efficacy versus established medication effectiveness, perceived compliance of tDCS versus medication. Results suggest tDCS is acceptable but depends on evidence of effectiveness and regular availability.